Doing time and the unemployment line: the impact of incarceration on ex-inmates’ employment outcomes - Emmert, Amanda D. (Crime & delinquency, 2019)
This study measures the influence multiple incarcerations and age at first incarceration have on the lengths of time ex-inmates are not employed and the amount of time ex-inmates spend looking for employment. Fixed-effects analyses of longitudinal data from the Rochester Youth Development Study (RYDS) finds a relationship between incarceration at younger ages and longer non-employment experiences, but no association between incarcerations between 23 and 32 years old and non-employment lengths. Meanwhile, these individuals who experience incarceration younger spend equivalent time looking for employment as their never-incarcerated peers, despite having nonequivalent periods without employment.